Uncovering promising management practices from national Centers for Independent Living. - Stone VI; Bauer SM; Montgomery ME; Usiak DJ (Journal of Vocational Rehabilitation, 2007)
This paper summarizes the second in a series of two research studies completed by the Rehabilitation Research and Training Center (RRTC) on Independent Living Management (ILM). The study identified management practices potentially effective for the organizational context of Centers for Independent Living (CILs) by 'taking stock' of current practices across the national network of CILs. Executive directors from a random sample of 131 CILs were interviewed over telephone, in a participatory research approach and using a two-dimensional Kano survey. Findings included 246 practices relevant to CIL management, and their perceived quality was reported using a Kano classification as 'expected', 'revealed', 'exciting' and 'no-difference' practices. They were further distributed under the 9 management areas of the CIL organizational profile collectively identified by a national sample of CIL stakeholders during our first study. A direct application of this knowledge relates to improving organizational performance, by empowering CILs to plan, train, manage, evaluate and advance their organizations. The study conducted a pilot follow-up to illustrate the implemented practices as part of organizational snapshots, a planning tool used by the RRTC-ILM.